Measuring intangible capital and its contribution to economic growth in Europe - Bart van Ark; Janet X. Hao; Carol Corrado; Charles Hulten (EIB Papers, 2009)
This study describes the state of the art in the measurement of intangible capital and its contribution to economic growth, with a focus on an international comparison of intangible investment intensity and intangible capital deepening among eleven advanced economies. By employing a broad measure of intangibles, including computerized information, innovative property and economic competencies, we find a relatively large impact on growth. Intangible capital explains about a quarter of labour-productivity growth in the US and larger countries of the EU. The continental West-European countries show a distinction between countries with significant contributions from intangible capital deepening and a group of laggards. Catching-up countries such as the Czech Republic, Greece and Slovakia show much larger contributions from tangible capital deepening than from intangibles, and also larger multi-factor productivity (MFP) growth rates related to the restructuring of those economies.
Keywords: 330; Immaterielles Anlagevermögen; Messung; Wirtschaftswachstum; Arbeitsproduktivität; Produktivität; Vergleich; EU-Staaten; USA